Direct Chromium Alloying by Chromite Ore with the Presence of Metallic Iron - Hu, Xianfeng; Teng, Lidong; Seetharaman, Seshadri (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Direct chromium alloying by chromite ore in EAF operation is a promising process in stainless steel production, which has the advantage of resource-saving, energy-saving, and environment-friendly. In the present investigation, iron, carbon, and chromite ore mixture (Fe+C+FeCr2O4) were chosen as the precursor for direct chromium alloying. Thermogravimetric Analysis (TGA) experiments were carried out to investigate the effect of iron content on the reduction kinetics, and the results show that the presence of metallic iron in the precursor will increase the reduction rate of chromite. Up-scaling experiments (100 g and 500 g scale) have been carried out in the induction furnace to further test the effectiveness of using industrial chromite ore for direct chromium alloying. The induction furnace tests confirmed the necessity of adjusting composition of the slags to ensure high yield of chromium in the final products; and chromium yield can reach 90%.